Uma proposta para ensinar a aceleração da gravidade: usando a interface Hackeduca conecta - Chagas, Sidney Assis (Brasil, 2022)
In our schools, the teaching of physics consists of passing on a pile of information without connection with the world that surrounds the student. Forgetting that Physics is a science that studies natural phenomena, through observation. In view of the above, the present work aims to develop a sequence of activities on free fall using the Hackeduca Conecta application, with experiments simulated by the same application, for students of the 1st grade of High School, following the pedagogical theory of Jerome Bruner that deals with “Discovery teaching”. The proposal consists of analyzing the movement of the bodies through the "Free Fall" where data will be programmed and collected through sensors and transmitted to the computer using Arduino, so we will be able to generate graphs to analyze the movement of the bodies, discuss values and assist students in solving problems through tests, analyze some important parameters in this phenomenon studied and also measure the value of gravity acceleration. It is hoped that this Teaching-Learning proposal will make student learning effective and very profitable in order to make the student an investigator and a critical-reflective thinker and that all this knowledge acquired by him be profitable in his reality.